Determinação simultânea de micotoxinas em cereais - Rossi, Natália Hoffmann (2019)
Mycotoxins are secondary metabolites produced by filamentous fungi present in oat and wheat and several foodstuffs consumed worldwide. When contaminated food items are ingested, they may be toxic to humans and animals. Thus, this study aimed to apply a qualitative screening method and quantify the mycotoxins with and without current legislation present in oat and wheat samples in 2016 and 2017 and in purple maize in 2017. Four hundred and sixty-five samples of oat (91) and wheat (374) from the states of Rio Grande do Sul and Santa Catarina states and 63 samples of Peuvian purple maize from Peru were analyzed. The frequency of occurrence and concentration of the following mycotoxins were determined: alternariolmetileter (AME), alternariol (AOH), tentoxin, neosolaniol, nivalenol (NIV), wortmannin, deoxynivalenol (DON), 3-acetyl deoxynivalenol, 15-acetyl deoxynivalenol, zearalenone (ZEA), aflatoxin B1 (AFB1), aflatoxin B2, aflatoxin G1, aflatoxin G2, fumonisin B1, fumonisin B2, fumonisin B3, ochratoxin A, ochratoxin α, T-2 toxin, HT-2 toxin, fusarenon x, cyclopiazonic acid, gliotoxin, agroclavin and citreoviridin. Mean levels of mycotoxins within the standards of the Brazilian legislation were found, but some of the detected metabolites do not present specifications for the studied cereals. The main mycotoxins detected in oat were AME and AOH, with a frequency of occurrence of 100 and 98%, respectively. These were also the main mycotoxins found in wheat, followed by NIV, DON, ZEA and AFB1, depending on the year of sample collection. For purple maize no mycotoxins were found in the Brazilian legislation. All mycotoxins present in the legislation had levels below the limit of quantification. The main mycotoxins found in purple maize were also AME and AOH, with frequency of occurrence of 14.3 and 7.9%, respectively It may be concluded that mycotoxins without guidance levels were detected in both cereals and years. Moreover, a warning must be made regarding the contamination at high concentrations by mycotoxins which are regulated, in some cases exceeding the permitted levels. For wheat and oatmeal samples, it may be concluded that in both years and cereals mycotoxins not included in the legislation were detected, and a warning must be made for the contamination by mycotoxins that are regulated, in some cases above the permitted levels. This is the first survey to analyze emerging mycotoxins in oats, wheat and purple corn.